SELERA PASAR TEH RUSIA TERHADAP TEH HITAM ORTHODOX CURAH - SUPRIHATINI, ROHAYATI (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
A study on tea market preference is required in order to increase market share of Indonesian tea in Russian Federation. Russian Federation market prefers a medium grown tea, which dominate broken grade (91%). Minimum requirement for all organoleptic attributes (appearance, taste, colour, flavour, and infused leaf) is medium score. Most of tea deffects are not accepted are only main deffects. Packaging, delivery, and payment method prefer are paper sack, Free on Board (FOB), and Letter of Credit (L/C), respectively.
Keywords: Tea, Market, Perference, Russian Federation